2020
DOI: 10.3389/fimmu.2020.568759
|View full text |Cite
|
Sign up to set email alerts
|

Combinational Immunotherapy for Hepatocellular Carcinoma: Radiotherapy, Immune Checkpoint Blockade and Beyond

Abstract: The systemic treatment landscape for advanced hepatocellular carcinoma (HCC) has experienced tremendous paradigm shift towards targeting tumor microenvironment (TME) following recent trials utilizing immune checkpoint blockade (ICB). However, limited success of ICB as monotherapy mandates the evaluation of combination strategies incorporating immunotherapy for improved clinical efficacy. Radiotherapy (RT) is an integral component in treatment of solid cancers, including HCC. Radiation mediates localized tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 132 publications
0
97
0
Order By: Relevance
“…Lee et al. reviewed ( 25 ) that radiotherapy enhanced immune infiltrates into the tumor microenvironment (TME) but induced upregulation of immune checkpoint molecules (PD-1, PD-L1) and VEGF. Moreover, anti-VEGF therapy promoted normalization of vessel formation, which improved the efficacy of radiotherapy and further boosted infiltration of cytotoxic cells into TME.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al. reviewed ( 25 ) that radiotherapy enhanced immune infiltrates into the tumor microenvironment (TME) but induced upregulation of immune checkpoint molecules (PD-1, PD-L1) and VEGF. Moreover, anti-VEGF therapy promoted normalization of vessel formation, which improved the efficacy of radiotherapy and further boosted infiltration of cytotoxic cells into TME.…”
Section: Discussionmentioning
confidence: 99%
“…103 Murine as well as clinical studies have shown that radiation can potentiate the cellular anti-cancer immune response by inducing cancer cell death and further sensitize tumors to ICIs. 104,105 In turn, the application of ICIs may revert radiation-induced exhaustion of cytotoxic T cells. 105,106 Based on the potential synergistic effects of percutaneous radiation and cancer immunotherapy, the combination of radiotherapy and ICIs is currently under investigation in HCC.…”
Section: Perioperative/interventional Therapymentioning
confidence: 99%
“…104,105 In turn, the application of ICIs may revert radiation-induced exhaustion of cytotoxic T cells. 105,106 Based on the potential synergistic effects of percutaneous radiation and cancer immunotherapy, the combination of radiotherapy and ICIs is currently under investigation in HCC. 105 Nevertheless, alongside initial response rates, long-term oncological outcomes and clinical safety need to be further evaluated.…”
Section: Perioperative/interventional Therapymentioning
confidence: 99%
“…Mounting evidence suggests local radiotherapy might promote immunogenic tumor cell death, and ICIs could favor a stronger immunologic anti-tumor reaction after treatment [ 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ]. Despite this, there is no published prospective clinical data on combined RT and ICIs therapy in HCC, except a few small series [ 134 ].…”
Section: Combination Of External Radiotherapy and Immunotherapymentioning
confidence: 99%